The Molecular Structure of Polymer-Fullerene Composite Solar Cells and Its Influence on Device Performance - Beal, R; Stavrinadis, A; Warner, J; Smith, J; Assender, H; Watt, A (2010)
Understanding the nanomorphology of polymer-based solar cells is key to improving device efficiencies. A detailed study of the changes in polymer solar cell morphology at the molecular level and in real time under process conditions is presented. Using low voltage, high resolution electron microscopy (LVHREM) we observe the mechanisms of PCBM-rich domain migration in real time and provide evidence for vertical segregation within the bulk heterojunction and increased crystallinity of both P3HT and PCBM. The results of the study highlights the fact that P3HT:PCBM bulk heterojunction morphology should be viewed within the framework of a four-phase, three-dimensional, nonequilibrium system. © 2010 American Chemical Society.